Rapid oxidation of iodide and hypoiodous acid with ferrate and no formation of iodoform and monoiodoacetic acid in the ferrate/I−/HA system. (1st November 2018) - Wang, Xianshi; Liu, Yulei; Huang, Zhuangsong; Wang, Lu; Wang, Yicheng; Li, Yanting; Li, Juan; Qi, Jingyao; Ma, Jun
Abstract: Toxic and odorous iodinated disinfection byproducts (I-DBPs) could form in the chemical oxidation of iodine-containing water. A critical step for controlling the hazardous I-DBPs is to convert the iodine species into stable and harmless iodate (IO3 − ) while inhibiting the accumulation of highly reactive hypoiodous acid (HOI). Herein, the oxidation of I − and HOI with ferrate was investigated, and the formation profile of HOI was determined based on 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonate) (ABTS) coloring method through a stopped-flow spectrophotometer. The second-order rate constants (kapp ) of ferrate with HOI decreased from 1.6 × 10 5  M −1 s −1 to 8.3 × 10 2  M −1 s −1 as the solution pH varied from 5.3 to 10.3, which were 7.5, 7.2 and 13.8 times higher than that of ferrate with I − at pH 6.0, 7.0 and 8.0, respectively. Compared with other oxidants such as ozone, hypochlorous acid, chloramine and potassium permanganate, ferrate would swiftly oxidize HOI formed in the I − oxidation process. For the ferrate oxidation of I-containing water, HOI was swiftly oxidized to IO3 − from pH 5.0 to 9.0. Phosphate buffer promoted the oxidation of I − while inhibited the oxidation of HOI with ferrate. When 5 mgC/L of humic acids (HA) existed in the solution, no formation of iodoform and monoiodoacetic acid (MIAA) was observed in the oxidation of iodide (20 μM) with ferrate (from 10 μM to 80 μM). These results suggested that ferrate oxidation could be an effective method for the control of I-DBPs in iodine-containing water treatment. Graphical abstract: Image 1 Highlights: ABTS coloring method was developed for determining HOI in stopped-flow spectrophotometer. Fe(VI) was more effective on I-DBPs control than that of O3, NH2 Cl, PMS and Mn(VII). No iodoform and MIAA formation was observed in the ferrate/I − /HA reaction system. Phosphate promoted the oxidation of I − while inhibited the oxidation of HOI with Fe(VI).